Age and growth of the threatened endemic skate Rioraja agassizii (Chondrichthyes, Arhynchobatidae) in the western South Atlantic - Caltabellotta, F. P.; Silva, F. M.; Motta, F. S.; Gadig, O. B. F. [UNESP] (Csiro Publishing, 2019)
The Rio skate Rioraja agassizii is a threatened endemic skate species frequently caught as bycatch in the western South Atlantic. However, there is no biological information about its age and growth parameters, which would be necessary to provide science-based information for the development of management strategies for this species. The aim of the present study was to provide information about the age and growth parameters of R. agassizii. In all, 138 vertebrae from individuals ranging in size from 9.0 to 53.2-cm total length (TL) were analysed. The edge analysis indicated a trend for annual band deposition in the vertebrae. Maximum ages estimated for males and females were 6 and 10 years respectively. Akaike's information criterion indicated that the modified two-parameter form of the von Bertalanffy growth function (using length at birth L-0 = 9.0 cm TL) provided the best fit, with derived parameters of theoretical maximum length L-infinity = 49.6 cm TL and growth coefficient k = 0.27 for males and L-infinity = 59.0 cm TL and k = 0.22 for females. Our results are important to understanding the resilience of this skate species to harvest, which can contribute to the development of fisheries management strategies and conservation programs.
Keywords: fisheries management; population dynamics; Rajiformes